Fibrinogen-to-prealbumin and C-reactive protein-to-prealbumin ratios as prognostic indicators in severe fever with thrombocytopenia syndrome - Zhang, Fan; Liu, Xiao-Yi; Qiao, Jin-Ping; He, Wen-Tao (Frontiers in Cellular and Infection Microbiology, 2024)
Background The primary aim of this study is to investigate the correlation between serum levels of fibrinogen-to-prealbumin ratio (FPR) and C-reactive protein-to-prealbumin ratio (CPR) and prognostic outcomes among patients with severe fever with thrombocytopenia syndrome (SFTS). SFTS, characterized by elevated mortality rates, represents a substantial public health challenge as an emerging infectious disease. Methods The study included 159 patients with SFTS. Clinical and laboratory data were compared between the survival and death groups. Univariate and multivariate logistic regression analysis were utilized to identify independent risk factors for mortality. The predictive efficacy of FPR and CPR was evaluated using receiver operating characteristic (ROC) curve. Survival analysis was conducted using the Kaplan–Meier curve and the log-rank test was employed for comparison. Results The death group exhibited significantly elevated levels of FPR and CPR compared to the survival group (P < 0.05). Multivariate logistic regression analysis confirmed that both FPR and CPR independently correlated with a poorer prognosis among patients with SFTS. The ROC curve analysis indicated that FPR and CPR had superior predictive capabilities compared to C-reactive protein and fibrinogen. Kaplan–Meier survival analysis demonstrated that patients with SFTS who have FPR > 0.045 (log-rank test; χ2 = 17.370, P < 0.001) or CPR > 0.05 (log-rank test; χ2 = 19.442, P < 0.001) experienced significantly lower survival rates within a 30-day follow-up period. Conclusion Elevated levels of FPR and CPR serve as distinct risk factors for mortality among patients with SFTS, indicating their potential to predict an unfavorable prognosis in these patients.